A Study on Chinese EFL Teachers' Work Engagement: The Predictability Power of Emotion Regulation and Teacher Resilience - Xie, Fei (Frontiers in Psychology, 2021)
Employing a sequential mixed-methods design, the current study examined the role of Chinese EFL teachers’ emotion regulation and resilience in predicting their work engagement. To this end, 314 Chinese EFL teachers with various academic degrees and teaching experiences were opted from different schools, institutes, and universities of China. To obtain the quantitative data, Utrecht Work Engagement Scale (UWES), Connor–Davidson Resilience Scale (CD-RISC), and Emotion Regulation Questionnaire (ERQ) were electronically distributed among participants. Performing correlational analyses, a strong association was found between teacher resilience and work engagement. The inspection of the correlations also revealed a moderate correlation between cognitive reappraisal and resilience as well as cognitive reappraisal and work engagement. To probe the predictability power of teacher resilience and emotion regulation (cognitive reappraisal), structural equation modeling (SEM) was performed. The results of the SEM analysis demonstrated that Chinese EFL teachers’ work engagement was predicted significantly and favorably by their resilience. Using semi-structured interviews, some qualitative data were also collected to fully understand Chinese EFL teachers’ perceptions of work engagement. The thematic analysis (TA) of Chinese EFL teachers’ responses to interview questions resulted in two main themes and fourteen sub-themes, revealing extrinsic and intrinsic factors contributing to teaching engagement. The findings of TA illuminated that both personal resources and job resources can predict teaching engagement. The pedagogical implications for administrators and teacher trainers are further discussed.